Identifying knowledge components in software requirement elicitation - Taheri, Laleh; Che Pa, Noraini; Abdullah, Rusli; Abdullah, Salfarina; Shafazand, Mohammad Yaser (IEEE (IEEE Xplore), 2014)
This paper considers the importance of knowledge in software development organizations which are highly knowledge-intensive and focuses on knowledge audit in their requirement elicitation process. Requirement elicitation process involves a great deal of knowledge and there are several problems regarding eliciting and using the knowledge in this process. Misunderstanding, undefined scope, conflicting information and constant changes of requirements are some of the problems of requirement elicitation. A knowledge audit model is proposed in this paper to improve the requirement elicitation process by identifying knowledge components and knowledge sources existing in the requirement elicitation process as well as their relationships. A survey is then conducted to prove the validity of the model. The results support that the proposed knowledge components and knowledge audit model improves requirement elicitation.